Proposed new interior design of Heritage Hotel for Heritage Station Hotel Sdn. Bhd. at No.2 Jalan Raja, 50500, Kuala Lumpur / Adiza Zaklin Razali - Razali, Adiza Zaklin (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is a proposal new interior design o f Heritage Boutique Hotel at Lot 2, Jalan Raja, 50500 Kuala Lumpur. This proposed boutique hotel is located in a strategic area of KL city which is the centre of attraction of the local and tourists, the Merdeka Square. Our main attraction is to the local and tourists. As we all know, a boutique hotel is a exclusive hotel that preserve with its own concept and identity. Even though, the price rate is quite expensive almost the same as a 4-star hotel rates, but the environment o f the room as if ‘your own home’. The concept and image o f a boutique hotel must be exclusive which reflected the category of the client. Connected to that, the chosen design style for the boutique hotel is based on heritage design that could represent the historical building, ‘back to history combining with the latest design trend would attract the guest with different perspective. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend to the boutique, types of services offered, spaces to be concluded in the proposed area, nature of business and information about other fashion boutique that use the same system in management, as the proposed hotel. Some o f the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.